Unlocking the biology of RAGE in diabetic microvascular complications - Manigrasso, Michaele B.; Juranek, Judyta; Ramasamy, Ravichandran; Schmidt, Ann Marie (Trends in endocrinology and metabolism, 2014)
•RAGE is a multi-ligand receptor whose families of ligands accumulate in diabetes.•RAGE contributes to the pathogenesis of the microvascular complications of diabetes.•Levels of soluble RAGEs may serve as biomarkers for diabetes and its complications. The discovery of the receptor for advanced glycation end-products (RAGE) set the stage for the elucidation of important mechanisms underpinning diabetic complications. RAGE transduces the signals of advanced glycation end-products (AGEs), proinflammatory S100/calgranulins, and high mobility group box 1 (HMGB1), and is a one of a family of receptors for lysophosphatidic acid (LPA). These ligand tales weave a theme of vascular perturbation and inflammation linked to the pathogenesis of the chronic complications of diabetes. Once deemed implausible, this concept of inflammatory cues participating in diabetic complications is now supported by a plethora of experimental evidence in the macro- and microvasculature. We review the biology of ligand–RAGE signal transduction and its roles in diabetic microvascular complications, from animal models to human subjects.